2016
DOI: 10.1159/000446376
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 in Renal Pathology: More Than Just an Innocent Bystander?

Abstract: Background: Galectin-3 is a member of a closely related lectin family, which is detected in several vertebrate epithelial and myeloid cell types. This beta-galactoside-binding soluble protein plays an important role in multiple biological processes. Depending on its location, type of injury or site of damage, the effects by galectin-3 can be various and sometimes contrasting. Summary: In this review, we discuss the general characteristics and functions of galectin-3. More specifically, we focus on the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 91 publications
(113 reference statements)
1
53
0
2
Order By: Relevance
“…Higher concentrations of Gal-3 may be associated with progression of CKD, indicating potential novel mechanisms related to Gal-3 expression that may contribute to the progression of CKD [25]. Furthermore, Gal-3 is reported to play a pivotal role in renal interstitial fibrosis and progression of CKD [117]. Thus, inhibition of Gal-3 may be a promising therapeutic strategy to prevent advanced renal disease.…”
Section: Gal-3 As a Biomarker Of Ckd In Clinical Studiesmentioning
confidence: 99%
“…Higher concentrations of Gal-3 may be associated with progression of CKD, indicating potential novel mechanisms related to Gal-3 expression that may contribute to the progression of CKD [25]. Furthermore, Gal-3 is reported to play a pivotal role in renal interstitial fibrosis and progression of CKD [117]. Thus, inhibition of Gal-3 may be a promising therapeutic strategy to prevent advanced renal disease.…”
Section: Gal-3 As a Biomarker Of Ckd In Clinical Studiesmentioning
confidence: 99%
“…Thus, the ability to cleave galectin-3 appears to be a preserved function in adherent staphylococcal species; both S. epidermidis and S. aureus form biofilms on medical devices (2,5), and it may be hypothesized that galectin-3 processing is associated not only with superficial skin infection but also with graft-related infection. S. saprophyticus, commonly causing urinary tract infection, lacked galectin-3-processing capacity even though galectin-3 is present throughout the urinary tract (46), in line with the lack of any known exoprotease expression in this species (47).…”
Section: Discussionmentioning
confidence: 81%
“…As a member of an evolutionarily conserved family of soluble β‐galactoside‐binding lectins, galectin‐3 is associated with the activation of macrophages and fibroblasts, which leads to inflammation and fibrosis . In the kidney, galectin‐3 is mainly expressed in epithelial cells in glomerular mesangium, distal tubules and proximal tubules . Pugliese et al has found that galectin‐3 could protect kidney from advanced glycosylation end products‐induced renal tissue injury in diabetic mice .…”
Section: Discussionmentioning
confidence: 99%